2014
DOI: 10.1111/jvp.12193
|View full text |Cite
|
Sign up to set email alerts
|

Comparative pharmacokinetics of norfloxacin nicotinate in common carp (Cyprinus carpio) and crucian carp (Carassius auratus) after oral administration

Abstract: Comparative pharmacokinetics of norfloxacin nicotinate (NFXNT) was investigated in common carp (Cyprinus carpio) and crucian carp (Carassius auratus) after a single oral dose of 10 mg/kg body weight (b.w.). Analyses of plasma samples were performed using ultra-performance liquid chromatography (UPLC) with fluorescence detection. After oral dose, plasma concentration-time curves of common carp and crucian carp were best described by a two-compartment open model with first-order absorption. The pharmacokinetic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…It was relatively higher in comparison with some other species of antibacterial agents in fish with similar temperature. In this respect, Xu et al reported that the K a value of norfloxacin nicotinate in plasma was 2.75/hr at 20°C for crucian carp after oral administration (Xu, Ai, Liu, & Yang, ), which was similar to the reported value of chloramphenicol (3.02/hr) in carp ( Cyprinus carpio L.) at 20°C (Huang, Sun, Li, & Huang, ). Moreover, it was found that the K a value of difloxacin was 1.27/hr at 20°C (Ding et al, ) and that of quinocetone was 1.65/hr in crucian carp at 24°C (Liu et al, ).…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…It was relatively higher in comparison with some other species of antibacterial agents in fish with similar temperature. In this respect, Xu et al reported that the K a value of norfloxacin nicotinate in plasma was 2.75/hr at 20°C for crucian carp after oral administration (Xu, Ai, Liu, & Yang, ), which was similar to the reported value of chloramphenicol (3.02/hr) in carp ( Cyprinus carpio L.) at 20°C (Huang, Sun, Li, & Huang, ). Moreover, it was found that the K a value of difloxacin was 1.27/hr at 20°C (Ding et al, ) and that of quinocetone was 1.65/hr in crucian carp at 24°C (Liu et al, ).…”
Section: Discussionsupporting
confidence: 64%
“…In this study, the plasma value of AUC was 15.12 mg hr/L. Ding et al reported that the AUC value of difloxacin in crucian carp was 355.2 mg hr/ml at 20°C after oral administration (Ding et al, ), which was much higher than that of quinocetone (126.6 µg hr/ml) with the same temperature (Xu et al, ). In addition, it was reported that there was a significant difference for AUC between low temperature group and high temperature group.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…Because of the unique structure of the intestinal tract in all Cyprinidae fish, fluoroquinolones are very easily absorbed and transferred into the bloodstream. For example, the bioavailability of enrofloxacin has been found to be as high as 86% . The wide use of fluoroquinolones in the production of livestock may also indirectly contribute toward the residual fluoroquinolones in fish muscle tissue and influence dietary safety .…”
Section: Discussionmentioning
confidence: 99%
“…Because of the unique structure of the intestinal tract in all Cyprinidae fish, fluoroquinolones are very easily absorbed and transferred into the bloodstream. For example, the bioavailability of enrofloxacin has been found to be as high as 86% [30][31][32][33].…”
Section: Occurrence Of Fluoroquinolones In Aquaculturementioning
confidence: 99%